A social neuroscience approach to conflict resolution: Dialogue intervention to Israeli and Palestinian youth impacts oxytocin and empathy. (4th July 2019) - Influs, Moran; Pratt, Maayan; Masalha, Shafiq; Zagoory-Sharon, Orna; Feldman, Ruth
ABSTRACT: The rapid increase in terror-related activities, shift of battlefield into civilian locations, and participation of youth in acts of violence underscore the need to find novel frameworks for youth interventions. Building on the Israeli-Palestinian conflict and social neuroscience models we developed an eight-week dialogue group-intervention for youth growing up amidst intractable conflict. Eighty-eight Israeli-Jewish and Arab-Palestinian adolescents (16-18years) were randomly assigned to intervention or control groups. Before (T1) and after (T2) intervention, one-on-one conflict interaction with outgroup member were videotaped, oxytocin levels assayed, attitudes self-reported, and youth interviewed regarding national conflict. We tested the hypothesis that dialogue intervention would enhance empathic behavior and increase oxytocin levels following interaction with outgroup member. Intervention increased youth perspective-taking on national conflict. Oxytocin increased from T1 to T2 only for adolescents undergoing intervention who improved perspective taking in the process. Structural equation modelling charted three pathways to behavioral empathy toward outgroup member at T2; via endogenous oxytocin, empathic cognitions, and dialogue intervention; however, an alternative model without the intervention arm was non-significant. Our findings highlight the important role of empathy in programs for inter-group reconciliation and support evolutionary models on the precarious balance between the neurobiology of affiliation and the neurobiology of outgroup derogation.